(untitled) (Revista de Medicina Clinica, 2021)
We are currently facing a new wave of the disease known as COVID-19, which is causing a serious public health problem in many countries and does not give up. Although it is true that every day more is known about the clinic and its management, there is still to know about its potential complications. In order to provide data of scientific interest, in this work we focus on the incidence of pneumomediastinum in patients affected by COVID-19, where its correct and early management could represent an important advance. In this work we describe the 3 cases found in a tertiary level hospital, among a total of 2516 patients hospitalized for COVID-19 from March 16 to November 30, 2020. The incidence in men has been very low and zero in women.